RECG Maintains Plastid and Mitochondrial Genome Stability by Suppressing Extensive Recombination between Short Dispersed Repeats - Odahara, Masaki (PLoS Genet, 2015)
Maintenance of plastid and mitochondrial genome stability is crucial for photosynthesis and respiration, respectively. Recently, we have reported that RECA1 maintains mitochondrial genome stability by suppressing gross rearrangements induced by aberrant recombination between short dispersed repeats in the moss Physcomitrella patens. In this study, we studied a newly identified P. patens homolog of bacterial RecG helicase, RECG, some of which is localized in both plastid and mitochondrial nucleoids. RECG partially complements recG deficiency in Escherichia coli cells. A knockout (KO) mutation of RECG caused characteristic phenotypes including growth delay and developmental and mitochondrial defects, which are similar to those of the RECA1 KO mutant. The RECG KO cells showed heterogeneity in these phenotypes. Analyses of RECG KO plants showed that mitochondrial genome was destabilized due to a recombination between 8–79 bp repeats and the pattern of the recombination partly differed from that observed in the RECA1 KO mutants. The mitochondrial DNA (mtDNA) instability was greater in severe phenotypic RECG KO cells than that in mild phenotypic ones. This result suggests that mitochondrial genomic instability is responsible for the defective phenotypes of RECG KO plants. Some of the induced recombination caused efficient genomic rearrangements in RECG KO mitochondria. Such loci were sometimes associated with a decrease in the levels of normal mtDNA and significant decrease in the number of transcripts derived from the loci. In addition, the RECG KO mutation caused remarkable plastid abnormalities and induced recombination between short repeats (12–63 bp) in the plastid DNA. These results suggest that RECG plays a role in the maintenance of both plastid and mitochondrial genome stability by suppressing aberrant recombination between dispersed short repeats; this role is crucial for plastid and mitochondrial functions.